Global analysis of SIQS model with nonlinear saturated contact rate. (2017) - Wei, Changcheng; Fang, Juanyan; Wei, Yanting
This article discusses a class SIQS epidemic model with constant input and nonlinear incidence, puts forward the equilibrium model and demonstrates the globally asymptotic stability of disease-free equilibrium and the endemic equilibrium.